Engineering the human soul: bulgarian children`s and young adult science fiction in the 20th century (Research Announcements "Heritage BG", 2025)
We can trace, through the artistic worlds created by the writers between 1950 and 1989, the way in which critics perceived Children`s and Young Adult science fiction - from the instrumental of ideological education of the younger generation to a tool provoking the reader’s imagination to think about the present, its real problems and perspectives which would have an effect on the future. On the one hand, the construction of a literary-historical background ofthe period is important. It traces the ways in which the new system channels the cognitive and educational function of science fiction; the ideological problems of the time, modeled by the political, socialtransformations. Onthe otherhand, it creates conditions of a different ideological environment which creates not just alternativeness, but freedom for a critical interpretation of contemporary world. References:Primary Sources:Atanasov, Z. (1955). Detskata literatura i zadachite na komunist-icheskoto vazpitanie. – Septemvri, 11, 155–162.Antonov, N. (1960). Chudnoto pateshestvie. Sofia.Georgiev, A. (1974). Poletat kam Purpurnia drakon. Plovdiv.Dilov, L. (1980). Zvezdnite priklyuchenia na Numi i Niki. Sofia.Dilov, L. (1983). Do rayskata planeta i nazad. Sofia.Kolarova, E. (1987). Shte ima li promyana? – ABV, 22 septemvri, s. 5.Lizhev, T. (1976). Gradinite na Mars. Varna.Miltenov, Y. (1968). Chiponosko na Lunata. Sofia.Slavov, A. (1965). Faktorat „X“. Sofia.Selyanov, V. (1964). Trevoga v Kosmosa. Sofia.Ukaz 172 (2000). Zakon za detskata literatura. In: Balgarskata detska literatura (antologia). Sofia, 430–431.Ukaz 123 (2000). Zakon za detskata i mladezhka knizhnina. In: Balgarskata detska literatura (antologia). Sofia, 432–437.Ukaz 150 (1946). Zakon za izmenenie i dopalnenie na Zakona za detskata i mladezhka knizhnina. – Darzhaven vestnik, 209, 13 septemvri.Ukaz 181 (1946). Pravilnik za prilagane na zakona za detska i mladezhka knizhnina. – Darzhaven vestnik, 275, 29 noemvri.Secondary Sources:Angelov, D. (1956). Zemyata pred gibel. Sofia.Ivanov, S. (1950). Fantastika i deystvitelnosty. – http://www.fandom.ru/about_fan/ivanovs_1.htmKonstantinova, E. (1987). Vaobrazhaemo i realno: Fantastikata v balgarskata hudozhestvena proza. Sofia.Konstantinova, E. (1986). Sporovete okolo fantastikata. – ABV, 29 may, s. 4.Milchev, A. (1986). Trudnata sadba na fantastikata. – Literaturen front, 13 fevruari, s. 2.Svetlinov, B. (1955). Edin den na Lunata. Sofia.Stapov, P. (1965). Gosti ot Mion. Sofia.Umlenski, I. (1951). Tezisi po detska literatura. Sofia.
Keywords: contemporary Bulgarian literature; children`s and young adult science fiction; communist ideology; operational criticism